Utility of intrapapillary capillary loops seen on magnifying narrow-band imaging in estimating invasive depth of esophageal squamous cell carcinoma - Sato, Hiroki; Inoue, Haruhiro; Ikeda, Haruo; Sato, Chiaki; Onimaru, Manabu; Hayee, BuHussain; Phlanusi, Chainarong; Santi, Esperanza Grace R.; Kobayashi, Yasutoshi; Kudo, Shin-ei (Endoscopy, 2015)
Background and study aims: Intrapapillary capillary loops (IPCLs) have been used to estimate histopathological atypia and the invasion depth of squamous cell carcinoma (SCC). The aim of this study was to evaluate the clinical significance of IPCLs.Patients and methods: A total of 358 consecutive patients with esophageal neoplasia on magnifying narrow-band imaging (M-NBI) were studied. The lesions were categorized according to the IPCL classification of Inoue et al. and were subsequently resected. Resected specimens were histopathologically analyzed to determine the invasion depth. The inter- and intraobserver agreements in the interpretation of IPCL images were also investigated.Results: A total of 446 lesions were diagnosed on M-NBI as IPCL type V lesions, which were further classified as 185 IPCL type V1, 109 type V2, 104 type V3, and 48 type Vn. Sensitivity and specificity of IPCL type V1-2 for invasion confined to the epithelium or lamina propria mucosa (m1-2) were 89.5 % (95 % confidence interval [CI] 85.4 % – 92.7 %) and 79.6 % (95 %CI 72.3 % – 85.7 %), respectively. Sensitivity and specificity of IPCL type V3 for invasion confined to the muscularis mucosa or slight submucosal invasion (m3-sm1) were 58.7 % and 83.8 %, respectively. Sensitivity and specificity of IPCL type Vn for deeper invasion (sm2-3) were 55.8 % and 98.6 %, respectively. Interobserver agreement was substantial (κ = 0.609, 0.641, and 0.705), as was intraobserver agreement (κ = 0.705 and κ = 0.819).Conclusion: Changes in the morphology of IPCLs on M-NBI correlated with the depth of SCC invasion, and results were reproducible and reliable among observers. Identification of IPCL type V1-2 proved useful for the intraprocedural identification of m1-2 lesions, which are considered an absolute indication for endoscopic resection.